2016
DOI: 10.1038/nchem.2625
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching of glass transition temperatures of azobenzene-containing polymers induces reversible solid-to-liquid transitions

Abstract: The development of polymers with switchable glass transition temperatures (T) can address scientific challenges such as the healing of cracks in high-T polymers and the processing of hard polymers at room temperature without using plasticizing solvents. Here, we demonstrate that light can switch the T of azobenzene-containing polymers (azopolymers) and induce reversible solid-to-liquid transitions of the polymers. The azobenzene groups in the polymers exhibit reversible cis-trans photoisomerization abilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
469
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 511 publications
(501 citation statements)
references
References 25 publications
6
469
1
8
Order By: Relevance
“…[24,25] Furthermore, few examples have demonstrated the photocontrolled switching of liquid and solid phases in azobenzene materials. [26][27][28][29] Given the importance of molecular arrangement in photoresponsive materials, self-assembly strategies that facilitate ordering of functional motifs are prudent. Recently, we reported on the synthesis of a class of well-defined and discrete end-functionalized siloxane oligomers that form highly ordered multidomain nanomaterials with sub-5 nm periodicities.…”
mentioning
confidence: 99%
“…[24,25] Furthermore, few examples have demonstrated the photocontrolled switching of liquid and solid phases in azobenzene materials. [26][27][28][29] Given the importance of molecular arrangement in photoresponsive materials, self-assembly strategies that facilitate ordering of functional motifs are prudent. Recently, we reported on the synthesis of a class of well-defined and discrete end-functionalized siloxane oligomers that form highly ordered multidomain nanomaterials with sub-5 nm periodicities.…”
mentioning
confidence: 99%
“…The latter mechanical induction resulted in the formation of complex pattern that can be read out by birefringence,a llowing the recording of fingerprint information.Phase transitions of materials triggered by external stimuli, including application of electric fields, [1] magnetic fields, [2] light, [3] shear, [4][5][6] or temperature changes, [7] are of great interest because structural rearrangements within the materials result in abrupt changes of material properties.A mong them, shear-induced disorder-order transitions in soft polymeric materials have been extensively investigated because they are important for the optimization of processing conditions within the oil and plastic industry as well as for the function and properties of cell membranes and biological fibers in nature. Ab iological fluid system is introduced in which anionic polypeptides are complexed with cationic surfactants.T he resulting fluids exhibited very sensitive isotropic-nematic transition triggered by shear.T he formed liquid crystal was preserved after cessation of mechanical stimulus.S elf-ordering behavior of the material was achieved through water flowa nd finger pressing.…”
mentioning
confidence: 99%
“…Phase transitions of materials triggered by external stimuli, including application of electric fields, [1] magnetic fields, [2] light, [3] shear, [4][5][6] or temperature changes, [7] are of great interest because structural rearrangements within the materials result in abrupt changes of material properties.A mong them, shear-induced disorder-order transitions in soft polymeric materials have been extensively investigated because they are important for the optimization of processing conditions within the oil and plastic industry as well as for the function and properties of cell membranes and biological fibers in nature. [8][9][10][11][12][13][14] Forinstance,isotropic-nematic (I-N) and isotropic-smectic (I-S) transitions were realized in amphiphile micellar solutions [8][9][10][11] and thermotropic liquid crystals (LCs) [12,13] under steady shear flow.H owever,i ti sh ard to stabilize the resulting ordered phases after cessation of shear, [8][9][10][11][12][13] which may limit harnessing their favorable properties.Therefore,maintaining an ordered state induced from an isothermal disordered phase in polymer fluids in absence of an applied shear force remains an important challenge.…”
mentioning
confidence: 99%
“…BCPs can form various microphase separated nanostructures [12]. The self-assembly of block copolymers is a promising platform for the fabrication of nanostructured materials and devices [13][14][15][16][17][18][19][20]. We previously reported that BCPs can be hierarchically structured by combining phase separation with laser interference ablation [10].…”
Section: Introductionmentioning
confidence: 99%